Detection of monohydroxylated polycyclic aromatic hydrocarbons in urine and particulate matter using LC separations coupled with integrated SPE and fluorescence detection or coupled with high‐resolution time‐of‐flight mass spectrometry. (1st February 2018) - Lintelmann, Jutta; Wu, Xiao; Kuhn, Evelyn; Ritter, Sebastian; Schmidt, Claudia; Zimmermann, Ralf
Abstract: A high‐performance liquid chromatographic (HPLC) method with integrated solid‐phase extraction for the determination of 1‐hydroxypyrene and 1‐, 2‐, 3‐, 4‐ and 9‐hydroxyphenanthrene in urine was developed and validated. After enzymatic treatment and centrifugation of 500 μL urine, 100 μL of the sample was directly injected into the HPLC system. Integrated solid‐phase extraction was performed on a selective, copper phthalocyanine modified packing material. Subsequent chromatographic separation was achieved on a pentafluorophenyl core–shell column using a methanol gradient. For quantification, time‐programmed fluorescence detection was used. Matrix‐dependent recoveries were between 94.8 and 102.4%, repeatability and reproducibility ranged from 2.2 to 17.9% and detection limits lay between 2.6 and 13.6 ng/L urine. A set of 16 samples from normally exposed adults was analyzed using this HPLC‐fluorescence detection method. Results were comparable with those reported in other studies. The chromatographic separation of the method was transferred to an ultra‐high‐performance liquid chromatography pentafluorophenyl core–shell column and coupled to a high‐resolution time‐of‐flight mass spectrometer (HR‐TOF‐MS). The resulting method was used to demonstrate the applicability of LC‐HR‐TOF‐MS for simultaneous target and suspect screening of monohydroxylated polycyclic aromatic hydrocarbons in extracts of urine and particulate matter.